Effect of Think-pair Share Learning Strategy on Secondary School Students Achievement in Computer Studies: Implications for Global Development - Nneka Rita Nnorom; Chinyere Francisca Okafor; Chisom Perpetua Okeke (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Improving students’ achievement in computer studies is essential in the digital era, where technological competence supports educational advancement and global development. However, conventional lecture-based instruction often limits students’ participation and collaborative learning. Student-centred strategies such as Think–Pair–Share (TPS) offer opportunities to enhance interaction, reflection, and deeper understanding of learning materials. Objective: This study examined the effect of the Think–Pair–Share learning strategy on secondary school students’ achievement in computer studies and investigated whether gender differences in achievement emerge when this strategy is used. Method: A quasi-experimental pre-test–post-test non-equivalent group design was employed. The population consisted of 6,982 Junior Secondary School Two (JSS2) students from 94 co-educational secondary schools in Anambra State, Nigeria. A sample of 393 students (169 males and 224 females) from nine intact classes in Aguata and Awka education zones participated. Data were collected using the Computer Studies Achievement Test (CSAT). Mean, standard deviation, and ANCOVA were used for analysis. Results: Students taught using TPS achieved significantly higher scores than those taught through the lecture method, with male students demonstrating slightly higher achievement. Contribution: This study provides empirical evidence supporting TPS as an effective student-centred strategy for improving achievement in computer studies. Conclusion: Integrating TPS into classroom practice can promote active participation and meaningful learning in secondary education.